Chapter Solar and Chthonic Deities in Ancient Anatolia: The Evolution of the Chthonic Solar Deity in Hittite Religion - Steitler, Charles Wayne (Studia Asiana, 2023)
The "Sun-goddess of the earth" and the less clearly defined category of "chthonic solar deities" of Hittite religion have been the objects of various studies in recent years. This paper aims to examine the significance of these categories of deities within the Hittite festival texts. Although the Sun-goddess of the earth achieves some prominence in local cult contexts, such as at Zippalanda and Nerik, she otherwise remains a marginal deity. This contrasts with her general significance in Hittite magical rituals. The chthonic solar deities represent a less tangible deity type that is associated with death and the netherworld, but that also does not attain overarching significance in the Hittite state pantheon. Finally, the paper addresses the question, to what cultural milieu can we trace the beginnings of the Sun-goddess of the earth? Efforts to identify her origins in the Hattian milieu of north-central Anatolia will be critiqued, favoring the Luwian milieu instead as the most likely from which the tradition of the Sun-goddess emerged, and later flourished in the magical traditions especially that became widespread in Hittite society of Late Bronze Age Anatolia.